STUDY OF ALLELIC POLYMORPHIZM OF (GATA)$_n$-CONTAINING LOCI IN THE PARTHENOGENETIC LIZARDS $Darevskia~dahli~(Lacertidae)$ (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
The genesis of mini- and microsatellite loci, which is under extensive study in humans and some other bisexual species, have been virtually overlooked in clonal mode of reproduction. In present study we use PCR-analysis to examine allelic polymorphism of two loci of D. dahli – Du 215 and Du 281-containing (GATA)n microsatellite cluster. Different levels of intrapopuliation and interpopuliation variability of these loci were found. Du 215 showed the highest polymorphism – 8 allelic variants. Three alleles were found for Du 281. The primers chosen for loci Du 215 and Du 281 were also used for PCR analysis of homologous loci in two presumptive parental bisexual species D. mixta and D. portschinski. The PCR products of the corresponding loci of the parental species had approximately the same size. These data on the structure of the DNA loci provide a possibility to study genetic diversity in the parthenogenetic species D. dahli.
Keywords: bisexual species; mini- and microsatellite loci; polymorphism; genetic diversity